Pemetaan Potensi Wisata di Kecamatan Bontoa Kabupaten Maros Melalui Sistem Informasi Geografis (SIG) - Mufadhdhal Ilham, Muhammad Dzakwan; Nyompa, Sukri; A, Amal; U, Uca; H, Hasriyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study uses qualitative research methods with a focus on 8 (eight) villages in Bontoa District, Maros Regency. The study is a survey study with observations on the existing tourism potential in the study location. The instrument in the study is a geographical information system application aimed at the creation or process of tourism potential mapping. The utilization of a global positioning system (GPS) is also required for the determination of the location points of tourist potential (tourist attraction) located in the study location. The researcher also utilized the records as a result of a visit/survey to the study site. The results of the study show that the level of tourism potential (tourism attraction) in Bontoa District, Maros Regency is quite promising natural resource potential such as knitted crab and various types of shrimp, such as windu, vaname, and shrimp api-api, oyster processing skills of the family as a source of crackers, fishermen. The presence of traditional musical traditions such as violin, harp, and gambus, which are often played in customary events and local celebrations is still preserved and can be a tourist attraction. The distribution of the level of tourist potential (tourist attraction) in Bontoa District, Maros Regency that is part of the area is coastal and karst, rocky cliffs, mountains, lakes, Rivers, as well as expanses of rice fields and embankments are assets to be protected and continue to preserve. The presence of human resources capable of managing tourist areas and government support to improve tourism in Bontoa district.